A facile route to segmented copolymers by fusing ambient temperature step-growth and RAFT polymerization. Issue 77 (13th September 2017) - Gegenhuber, Thomas; Schenzel, Alexander M.; Goldmann, Anja S.; Zetterlund, Per B.; Barner-Kowollik, Christopher
Abstract : We introduce the facile synthesis of segmented copolymers via a catalyst-free Diels–Alder (DA) reaction at ambient temperature via step-growth polymerization and subsequent reversible addition fragmentation chain transfer (RAFT) polymerization. Abstract : We introduce the facile synthesis of segmented copolymers by a catalyst-free Diels–Alder (DA) reaction at ambient temperature via step-growth and subsequent reversible addition fragmentation chain transfer (RAFT) polymerization. High molecular weight step-growth polymers are readily obtained ( M w = 40 000 g mol −1 ), featuring trithiocarbonate moieties in their chain, which allow monomer insertion via RAFT polymerization yielding high molecular weight species.